EMOTIONAL INTELLIGENCE AND PEER SOCIAL SUPPORT AS PREDICTORS OF QUARTER-LIFE CRISIS IN EARLY ADULTHOOD - Namira Rana Tsabita; Iranita Hervi Mahardayani (SOSIOEDUKASI, 2025)
Quarter-life crisis is an emotional crisis period characterized by anxiety, self-doubt, and instability in the transition phase from adolescence to adulthood. The research method used a quantitative approach with a correlational design. The purposive sample was 122 respondents who were fresh graduates, unemployed, and confused about their life direction. Data were collected through a Likert scale that was tested for its validity and reliability, and then they were analyzed using multiple regression and Pearson correlation. The results showed a significant negative relationship between emotional intelligence and peer social support on the level of quarter-life crisis, with an effective contribution of 24% and 6.6%, respectively. The majority of respondents had a moderate level of quarter-life crisis, emotional intelligence, and peer social support. These findings indicate that high emotional intelligence and adequate peer social support play an important role in reducing the level of quarter-life crisis in early adulthood. This study has scientific contributions and practical recommendations for the development of psychological well-being in the early adulthood developmental phase, although it has limitations regarding the online data collection method and focuses on one age group.